The classroom management issues faced by early childhood teachers - Algamdi, Sharefah Saad (Journal of Educational and Psychological Sciences, 2024)
The study aimed to identify the classroom management problems faced by early childhood teachers, the study used the descriptive analytical method, the study sample consisted of (55) early childhood teachers, The study used one tool, which was a questionnaire, to collect data, The results of the study reached: The arithmetic mean of the response of the study sample members on the first axis: classroom management related to the teacher was equal to (2.61), While the arithmetic mean of the response of the study sample members on the second axis: classroom management related to the teacher’s classroom management was equal to (3.02), When the arithmetic mean of the response of the study sample members on the third axis: related to classroom management problems related to children was equal to (2.92), The arithmetic mean of the response of the study sample members to the fourth axis: related to classroom management problems related to the classroom and school environment was equal to (3.01), Also, the arithmetic mean of the study sample’s response to the fifth axis: related to classroom management problems related to parents was equal to (2.94), The study also found that there were no statistically significant differences at the significance level (0.05) in the responses of the study sample towards the classroom management problems faced by early childhood teachers according to the variable of experience in education and academic qualification, The study recommended the necessity of working to reduce the teaching quorum for early childhood teachers, taking into account the difference in the early childhood teacher’s specialization from the subjects she teaches, and also working to have the early childhood teacher teach a small number of subjects that are appropriate to her specialization.